Implementation of Pushing Reminder Technique for Women During The First Stage of Labor and Perineal Rupture Events - Ratnasari, Febi; Imanuddin, Bayu; Febriyani, Fitria (Universitas Muhammadiyah Yogyakarta, 2020)
Background: Rupture of the birth canal or perineal tear cannot be considered a minor injury because it contributes to maternal morbidity and mortality. The perineal rupture causes pain and can increase until the seventh day. Perineal rupture also causes 4-5% of mortality in postpartum mothers.Objective: The purpose of this study is to find out the effect of pushing reminder technique implementation on women during the first stage of labor and perineal rupture event.Method: The research method used was pre-experimental with Â intact group comparison design (post-test only control with 15 control respondents and 15 intervention respondents).Results: The results showed that the average age of the respondents was 26 years old with status as a housewives (93.3%), and the majority of the educational background was high school graduate (86%). By using the Mann-Whitney test, the results of alpha is 0.05 (0.369), so there is no relationship between the reminder of pushing technique and the occurrence of perineal rupture.Conclusion: There are other factors that affected the tears of the perineum such as babyâ€™s weight, previous history of perineal rupture, the rigidity of perineal muscles and lack of skills of health care providers to hold the perineum at the moment of babyâ€™s head expulsion, this indicated that is no relationship between the reminder of pushing technique and the occurrence of perineal rupture.Recommendation: It is adviced for Public Health Care Center is to provide educational media containing information for pregnant woman in a form of electronic media in the waiting room and through education of pregnant women regarding labor and perineum tear so that pregnant women understand the causes of perineal tear.